Brief vs Thong Hygiene in Obstetrics and Gynecology (B-THONG): A Survey Study [1J]. (May 2018) - Hamlin, Alyssa; Sheeder, Jeanelle; Muffly, Tyler
Abstract : INTRODUCTION: The goal of this study is to determine if thong underwear use is associated with a higher report of urinary tract (UTI) or vaginal infections (bacterial vaginosis; BV and yeast vaginitis; YV). METHODS: A national, cross-sectional survey regarding underwear type usage and infectious history was designed and distributed to women via a crowd-sourcing service. Parametric and non-parametric statistical methods were used to compare thong wearers to never-thong wearers. Thong wearers were defined as women who had worn a thong at any point in the last 12 months. RESULTS: 987 respondents met inclusion criteria and completed the survey; 315 (31.9%) were never-thong wearers and 672 (68.1%) were thong wearers in the last 12 months. Thong wearers were younger, thinner, and had different sexual and hygiene behaviors than never-thong wearers, including being more sexually active. Thong wearers were more likely to report UTIs (20.4% vs 11.4%; OR;95%CI: 1.99;1.23-2.95), yeast vaginitis (22.4% vs.15.6%; OR;95%CI: 1.61;1.13-2.30), and BV (9.7% vs. 5.7%; OR;95%CI:1.77;1.03-3.03) in the last 12 months. However, a logistic regression model found that only oral sex was found to be predictive of UTI (aOR;95%CI:1.61;1.07-2.43) and BV (aOR;95%CI: 2.63;1.39-4.97); further non-cotton crotch underwear (aOR;95%CI:1.75;1.17-2.62) and oral sex (aOR;95%CI:1.51; 1.02-2.25) were predictors of YV. CONCLUSION: We found that thong use is not associated with UTI, BV, or VY. Instead, sexual behaviors and hygiene choices are risk factors for these infections. We recommend that providers take a more complete sexual history to identify these risk factors rather than focusing on underwear as a primary risk factor.